Integrated and correlative high-throughput and super-resolution microscopy - Gunkel, Manuel; Flottmann, Benjamin; Heilemann, Mike; Reymann, Jürgen; Erfle, Holger (Histochemistry and cell biology, 2014)
We have developed a method to perform microscopic temporal and spacial multi-scale experiments by imaging cellular phenotypes of interest on complementary fluorescence microscopy systems. In a low-resolution fast data acquisition screen for phenotypic cellular responses induced by small interfering RNA (siRNA), cells in spots of siRNA cell arrays showing characteristic alterations have been selected automatically by feature space analysis. These objects were imaged on a second super-resolution dSTORM microscope (direct stochastic optical reconstruction microscopy). The coordinate transfer was based on fixed cells as reference points without the use of additional fiducial markers. This procedure is suitable to combine any kind of fluorescence microscopy technique, in order to gain further insights on the observed specimen at multiple temporal or special scales.
Gesehen am 20.08.2020